Evaluation of an Additive-Manufactured Acoustic Metamaterial as an Nacelle Liner using the Active Noise Control Fan - Bennett, Gareth (American Institute of Aeronautics and Astronautics, 2023)
This paper examines the performance of a 3D printed acoustic metamaterial as an acoustic treatment for aircraft engine nacelles in the Advanced Noise Control Fan. As the level of air travel continues to increase, so too does the demand for better noise-reduction technologies for aircraft. Engines are one of the two main sources of noise generated by aircraft, with fan noise, in particular, being of concern due to its broadband and tonal contributions. Small and lightweight methods of addressing both broadband and tonal noise are necessary due to the limits presented by the current engine design. Presented in this paper is a novel acoustic metamaterial which has undergone design optimisation for broadband noise reduction. The final design was produced using 3D printing and tested using the Advanced Noise Control Fan at the University of Notre Dame. It is seen that the material is capable of reducing the first harmonic of the blade passing frequency by up to 18.5 dB, with an overall noise reduction of 3.7 dB.
AIAA AVIATION 2023 Forum